(untitled) (Philological Studies, 2019)
Images (representations) about the countries and nations are being researched in different sciences and disciplines such as sociology and social psychology, imagology, cultural studies, tourism and marketing, applied linguistics, second-language teaching. There are auto- and hetero-images (about one’s own people and country and about others). When a language is taught as L2 in a heterogeneous group of students (considering their L1, country and cultural background) in a country where the target language is spoken, that multicultural environment confronts both students and instructors with different perceptions (both auto- and hetero-images) that affect the attitude of students to each other, and to the target language. The results of the survey conducted among beginner level students of the Croatian as L2 in Croaticum on how they see Croatia and Croats will be used as an attempt of getting an insight into their perceptions of Croatia and Croats and whether there are differences in images due to the fact which country students come from. Moreover it will be shown how the knowledge of this challenging subject can be applied in the teaching process, especially in its very important part nowdays – the acquisition of intercultural competence.